ADAPTASI KEBIASAAN BARU DI MASA PANDEMI COVID-19: Studi Pendekatan Ushul Fiqih dan Psikologi - Nihayatur Rohmah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
The Covid-19 pandemic has succeeded in changing the habits that we do every day at home, at school, at work, on the road, at the right place of worship and anywhere. New habits for healthier living must be continuously carried out in society and in every individual, so that they become social norms and new individual norms in everyday life. If the new habit is not carried out in a disciplined manner or is only carried out by a group of people, then this could be a threat that the corona virus outbreak will have a longer duration. Old habits that are often carried out, such as shaking hands, crowding / clustering, lazy to wash hands must begin to be abandoned because they support the transmission of Covid-19. Various responses and reactions are shown by the community, some are sad, anxious, afraid, anxious, worried, angry but there are also those who are calm or remain confident. Changing attitudes and behavior in society requires struggles in the form of adaptation or adjustment. Individuals in society always describe themselves with their changing environment, either autoplastically or alloplastically. Thus the relationship between Individuals who interact are always a relationship that influences each other (reciprocally). The adaptation of new habits in this pandemic period is not without purpose. Among them are as a community medium for survival and Conformity which is carried out openly so that it is visible to the public, with the aim of making individuals accepted in group or avoid Rejection from the group. The adaptation of this new habit in the pandemicovid-19 period is in accordance with the principle of benefit because in essence every commandment and prohibition of sharia